Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1097/00019514-199201010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Continuous quality improvement in the clinical setting

Abstract: Our ability to involve physicians in Continuous Improvement depends on our understanding of (1) professional norms and behaviors, (2) how organizational structures and systems affect physicians, and (3) basic adoption processes within health care organizations and by their professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Through extensive research, the obstacles associated with each dimension have been identified (Berwick, Godfrey, and Roessner 1990;Gaucher and Coffey 1993 Shortell et al (1996, 159). care Organizations 1992; Kaluzny, McLaughlin, and Kibbe 1992;Melum and Sinoris 1993;O'Brien et al 1994;Sahney and Warden 1991;Shortell et al 1995b;Quality Letter 1993). The cultural obstacles (Shortell et al 1995a) arise when organizations look inward to the needs of their professionals, rather than outward to the needs of their customers, or when physicians do not become involved because of inexperience or resistance to working as members of teams, or because they perceive that CQI is primarily a cost-control mechanism (McLaughlin and Kaluzny 1990).…”
Section: Strengths and Limitations Of The Cqi Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Through extensive research, the obstacles associated with each dimension have been identified (Berwick, Godfrey, and Roessner 1990;Gaucher and Coffey 1993 Shortell et al (1996, 159). care Organizations 1992; Kaluzny, McLaughlin, and Kibbe 1992;Melum and Sinoris 1993;O'Brien et al 1994;Sahney and Warden 1991;Shortell et al 1995b;Quality Letter 1993). The cultural obstacles (Shortell et al 1995a) arise when organizations look inward to the needs of their professionals, rather than outward to the needs of their customers, or when physicians do not become involved because of inexperience or resistance to working as members of teams, or because they perceive that CQI is primarily a cost-control mechanism (McLaughlin and Kaluzny 1990).…”
Section: Strengths and Limitations Of The Cqi Approachmentioning
confidence: 99%
“…The role of physicians in CQI work merits special attention. Many investigators have stressed the importance of early physician involvement and support to successful quality improvement efforts (Blumenthal and Edwards 1995;Conway, Keller, and Wennberg 1995;Horne 1996;Kaluzny, McLaughlin, and Kibbe 1992;Lammers et al 1996;Maleka and O'Connor 1995;McEachern 1993;Mosser 1996;.…”
Section: Physician Involvementmentioning
confidence: 99%
“…The loss of participants from Test Group 1 may also indicate that the topic and intensity of the intervention may not have matched their needs or learning styles. Attributes of health care professionals that may constitute barriers to the implementation of quality management principles, such as professional autonomy and independent working patterns, have been described (24,25). Medical practitioners may be more inclined to embrace the philosophies of quality improvement than dentists, because of their attachments to institutions such as hospitals where these concepts are implemented on an institutional basis (25) and are linked frequently to external accreditation of the institution.…”
Section: Substantive Issuesmentioning
confidence: 99%
“…Review the work plan and decide which meetings truly require the physicians' attendance and input. Make the physicians "invited members" at other meetings (Kaluzny, McLaughlin, & Kibbe, 1992).…”
Section: Be Sensitive To Physicians' Schedulesmentioning
confidence: 99%